Exotic birds increase generalization and compensate for native bird decline in plant–frugivore assemblages - García, Daniel; Martínez, Daniel; Stouffer, Daniel B; Tylianakis, Jason M; Van Veen, Frank (The Journal of animal ecology, 2014)
Exotic species are thought to alter the structure of natural communities and disrupt ecosystem functioning through invasion. Nevertheless, exotic species may also provide ecological insurance when they contribute to maintain ecosystem functions after the decline of native species following anthropogenic disturbance. Here, this hypothesis is tested with the assemblage of frugivorous birds and fleshy‐fruited plants of New Zealand, which has suffered strong historical declines in native birds while simultaneously gaining new frugivores introduced by European settlers. We studied the plant–frugivore assemblage from measures of fruit and bird abundances and fruit consumption in nine forest patches, and tested how this changed across a gradient of relative abundance of exotic birds. We then examined how each bird species' role in the assemblage (the proportion of fruits and the number of plant species consumed) varied with their relative abundance, body size and native/exotic status. The more abundant and, to a lesser extent, larger birds species consumed a higher proportion of fruits from more plant species. Exotic birds consumed fruits less selectively and more proportionate to the local availability than did native species. Interaction networks in which exotic birds had a stronger role as frugivores had higher generalization, higher nestedness and higher redundancy of plants. Exotic birds maintained frugivory when native birds became rarer, and diversified the local spectrum of frugivores for co‐occurring native plants. These effects seemed related to the fact that species abundances, rather than trait‐matching constraints, ultimately determined the patterns of interactions between birds and plants. By altering the structure of plant–frugivore assemblages, exotic birds likely enhance the stability of the community‐wide seed dispersal in the face of continued anthropogenic impact.